Role of Exogenous Hsp72 on Liver Dysfunction during Sepsis - Tsai, Tsen-Ni (Biomed Res Int, 2015)
This study examined the role of exogenous heat shock protein 72 (Hsp72) in reversing sepsis-induced liver dysfunction. Sepsis was induced by cecal ligation and puncture. Liver function was determined on the basis of the enzymatic activities of serum glutamate oxaloacetate transaminase (GOT) and glutamate pyruvate transaminase (GPT). Apoptosis was determined using terminal deoxynucleotidyl transferase dUTP nick end labeling staining. B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax), cleaved caspase-3 and caspase-9, and cleaved poly (ADP-ribose) polymerase (PARP) protein expressions were analyzed using Western blotting. Results showed GOT and GPT levels increased during sepsis, and levels were restored following the administration of human recombinant Hsp72 (rhHsp72). Increased liver tissue apoptosis was observed during sepsis, and normal apoptosis resumed on rhHsp72 administration. The Bcl-2/Bax ratio, cleaved caspase-3, caspase-9, and PARP protein expressions in the liver tissues were upregulated during sepsis and normalized after rhHsp72 treatment. We conclude that, during sepsis, exogenous Hsp72 restored liver dysfunction by inhibiting apoptosis via the mitochondria-initiated caspase pathway.